Peningkatan Kompetensi Pajak dengan Pelatihan Perhitungan PPh 21 Berbasis Tarif Efektif Rata-rata pada Guru Akuntansi SMK di Kota Yogyakarta: Enhancing Tax Competence through Income Tax Article 21 Calculation Training Based on the Average Effective Rate for Vocational High School Accounting Teachers in Yogyakarta City - Hidayah, Nurul; Sukirno, Sukirno; Hutama, Ponty Sya'banto Putra; Sayekti, Fitria Ningrum (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Income Tax (PPh) Article 21 is an essential aspect of financial administration that educators in accounting, particularly vocational high school (SMK) teachers, must master. However, many accounting teachers still struggle to understand the latest calculation methods, especially the application of the Average Effective Rate (TER) in line with the most recent tax regulations. This lack of understanding may lead to errors in teaching students and in practical application in the workplace. Therefore, systematic and practical training is needed to enhance accounting teachers' competence in calculating PPh 21 using the TER method. This training aims to improve teachers' understanding of PPh 21 and TER, provide practice in accurately calculating PPh 21 using TER, and assist in developing teaching materials relevant to industry needs. Through an applied approach, teachers are expected to become more confident in teaching taxation to students, thereby enabling SMK graduates to gain a firmer grasp of taxation. The expected outcomes of this training include improving teachers' competence in calculating PPh 21 with TER, producing a training module as a teaching guide, and publishing an article in a community service journal based on the training results. With this activity, it is expected that the quality of tax accounting education in vocational high schools will improve, bringing long-term benefits to both educators and students.